Posttraumatic growth, purpose, and trauma in university survivors of sexual assault - Damiani, Taylor; Sharkey, Jill D.; Morgan, Melissa L.; Mullin, Alice (Journal of American college health, 2025)
Objective: This study focused on purpose as a key mechanism of posttraumatic growth for university student survivors of sexual assault. Participants: An online survey was completed by 278 participants of various ethnic, racial and gender backgrounds, recruited through email, social media, department subject pools, and Amazon Mechanical Turk. Methods: Researchers used mixed methods, concurrent triangulation approach in which quantitative and qualitative data were collected simultaneously with closed and open-ended questions. Results: Hierarchical multiple regression demonstrated that age, purpose in life, high magnitude stressors, and trauma history were significantly related to posttraumatic growth. Emergent themes described the impacts of sexual assault, how sexual assault impacts purpose, and ways in which purpose impacted posttraumatic growth. Conclusion: Results confirmed the association of purpose with posttraumatic growth as well as other key impacts of trauma that should be investigated further. Next steps include evaluating therapeutic interventions focused on purpose.